Nursing students’ metaphorical perceptions of professional communication and the concept of nursing in their first clinical practice: qualitative research - Ayşegül Yıldız İçigen; Sinem Sönmez (BMC Nursing)
Abstract Background Nursing education combines theoretical knowledge and clinical practice to prepare nursing students to meet the evolving demands of healthcare services. Understanding nursing students’ metaphorical perceptions of the nursing profession and professional communication during their first clinical experiences can provide valuable insights into their professional identity and communication skills, as well as giving information about necessary improvements in nursing education. This study aimed to reveal the metaphorical perceptions of nursing students regarding the concepts of professional communication and nursing during their first clinical practices. Methods The study was conducted using a phenomenological design, a qualitative research method. A “student information form” and a “metaphor form,” developed by the researchers, were used as data collection tools. Participants’ sociodemographic data were analyzed on the Statistical Package for Social Sciences (SPSS). The analysis and evaluation of the metaphors used by nursing students for the concepts of nursing and professional communication were carried out in five stages by following the characteristics outlined in the qualitative data analysis approach called Metaphor Analysis. The Consolidated Criteria for Reporting Qualitative Research (COREQ) checklist was followed in the study. Results All 45 participants in the study were first-year nursing students, with 81.0% being female and the average age being 19.88 ± 0.96 years. Of the participants, 66.7% had chosen the nursing department willingly, and 57.1% had preferred it due to job opportunities. Participants generated 35 metaphors for the nursing profession, which were categorized into four groups, and 32 metaphors related to professional communication, which were classified into six groups. Conclusion The metaphorical perceptions of nursing students during their first clinical practices provided profound insights into how they experienced professional communication and the nursing profession. These metaphors are of great importance in understanding the challenges, the skills gained, and the emotional responses encountered during the students’ professional development processes.